2020
DOI: 10.1101/2020.08.27.266551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bundle-specific associations between white matter microstructure and Aβ and tau pathology at their connecting cortical endpoints in older adults at risk of Alzheimer’s disease

Abstract: Beta-amyloid (Aβ) and tau proteins, the pathological hallmarks of Alzheimer’s disease (AD), are believed to spread through connected regions. Combining diffusion imaging and positron emission tomography, we investigated associations between Aβ, tau and white matter microstructure specifically in bundles connecting brain regions in which AD pathology accumulates. In 126 cognitively normal elderly at risk of AD, we focussed on free-water corrected diffusion measures in the cingulum, posterior cingulum, fornix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
2
0
0
Order By: Relevance
“…However, further adjustments for the GM volume of the MTL regions decreased the effect size suggesting that the tau-FC association is not entirely independent from GM atrophy. Consistent with our findings, prior works have identified an association between increased tau-PET uptake and WM alterations in temporoparietal pathways (Binette et al, 2021;Luo et al, 2021;Jacobs et al, 2018;Strain et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, further adjustments for the GM volume of the MTL regions decreased the effect size suggesting that the tau-FC association is not entirely independent from GM atrophy. Consistent with our findings, prior works have identified an association between increased tau-PET uptake and WM alterations in temporoparietal pathways (Binette et al, 2021;Luo et al, 2021;Jacobs et al, 2018;Strain et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of an association between amyloid accumulation and WM degeneration, as suggested by our results, is in agreement with previous reports using both DTI (Strain et al, 2018) and FBA (Mito et al, 2018). In contrast, other studies have shown either a negative or a positive correlation between FBA-or tensor-derived metrics with global Aβ-PET uptake in different stages of AD (Dewenter et al, 2022;Luo et al, 2021;Binette et al, 2021;Benitez et al, 2022). Although the observed discrepancy might arise from differences in the selection of participants or analytical approach, our results suggest that tau aggregation is more closely linked to WM alterations than Aβ pathology.…”
Section: Discussionsupporting
confidence: 92%